Indacaterol/glycopyrronium: a dual bronchodilator for COPD. Issue 1 (January 2018) - Banerji, Donald; Fogel, Robert; Patalano, Francesco
Highlights: Development of IND/GLY was driven by a need to improve standards in COPD care The Phase 3 IGNITE program showed that IND/GLY is effective and well-tolerated The program helped elucidate the place for LABA/LAMA FDCs in treatment guidelines Availability of IND/GLY has helped optimise clinical practices in COPD management Further research may confirm how dual bronchodilation can maximise patient care. Abstract : Indacaterol/glycopyrronium (IND/GLY) 110/50 mcg was the first once-daily, long-acting β2 -agonist (LABA)/long-acting muscarinic antagonist (LAMA) fixed-dose combination (FDC) approved in Europe for the treatment of chronic obstructive pulmonary disease (COPD). Development of IND/GLY was driven by the need to improve the standard of care for patients with this disease, in terms of symptom control and exacerbation frequency. IGNITE, an adaptive, comprehensive, and innovative Phase 3 development program, demonstrated the efficacy of IND/GLY in optimising bronchodilation, reducing symptoms, and reducing exacerbations in patients with COPD. IGNITE challenged contemporary thinking about the pharmacological treatment and management of patients with this disease.